Investigating the adsorption of oxygen species on halogen-substituted monovacant graphene via density functional theory calculation - Geronia, Reynaldo M. III; Ocon, Joey D. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Electrochemical oxygen reduction reaction (ORR) plays an important role in the operation of fuel cells. However, this reaction is notoriously slow and hence, fuel cells must rely heavily on expensive materials like platinum to catalyze the reaction. Graphene, an easily synthesized and modified material, is now becoming the interest of researchers working on ORR catalysis. Modification usually involves doping with p-block elements, including halogens. However, most works in halogen doping emphasize functionalization; substitutional doping, on the other hand, has not yet been investigated. In this work, we use density functional theory calculations to show how halogens (X = F, Cl, Br, I) affect the properties of monovacant graphene. Furthermore, we introduce monatomic and diatomic oxygen to these halogen-substituted substrates to give insight on how these materials potentially support oxygen adsorption, which is a key step in the catalysis of ORR. With the reaction in mind, we explain the implications of structural and electronic features of oxygen-adsorbed systems on ORR catalysis.
Thesis (Master of Science in Energy Engineering)--University of the Philippines Diliman
Keywords: Electrolytic reduction; Fuel cells; Graphene